2011
DOI: 10.1002/crat.201100230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduced working frequencies on the floating‐zone growth of silicon single crystals

Abstract: Lowering the working frequency in the inductively heated floating zone growth of Si Single crystals will reduce the risk of arcing at the induction coil. This is of particular interest in the growth of large diameter crystals. In the current paper we present results from growth experiments at lower frequencies, 2 MHz and 1.7 MHz. It is found that the growth of dislocation-free crystals is possible at these frequencies and cause distinct changes in the interface deflection and radial resistivity profiles. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In FZ growth experiments arc discharges at the main slit reproducibly occurred without using a quartz plate in a pure Ar‐atmosphere during growth at cone diameters between 60 mm to 80 mm and frequencies of 2.8–3.0 MHz. These results agree with those found in previous experiments . Under equal process conditions, even under pure Ar‐atmosphere, a quartz plate allowed to increase the diameter of the crystal up to 125 mm, before arcing was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In FZ growth experiments arc discharges at the main slit reproducibly occurred without using a quartz plate in a pure Ar‐atmosphere during growth at cone diameters between 60 mm to 80 mm and frequencies of 2.8–3.0 MHz. These results agree with those found in previous experiments . Under equal process conditions, even under pure Ar‐atmosphere, a quartz plate allowed to increase the diameter of the crystal up to 125 mm, before arcing was observed.…”
Section: Resultsmentioning
confidence: 99%
“…A third option is a reduction of the frequency of the inductor current, as with lower frequency less voltage is required. Previously, it has been shown that reducing the frequency down to the range of 2 to 1.7 MHz prevents arcing for crystal diameters of 4–5 inch, at those experimental conditions were arcing occurred at higher frequencies between 2.8–3.0 MHz . Unfortunately, lower frequencies cause an inhomogeneous melting of the feed rod.…”
Section: Introductionmentioning
confidence: 99%
“…Using the 4-point probe method, radial resistivity distributions were measured in the lateral direction, at a longitudinal cross-section of the cylindrical part of the grown crystals. Numerical simulations of the convection streams in the melt were made using the commercially available programs SINGULA and ANSYS [5]. To investigate the influence of reduced frequencies on the electrical breakthrough behavior (arcing), three crystals were grown at the corresponding frequencies using pure argon as growth atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Menzel [65] uses the measured interface shapes to calculate the 3D EM field of different frequencies using the commercial code SINGULA and applying these results for the calculation of 2D fluid flow using the commercial code ANSYS-CFX.…”
Section: Historical Overviewmentioning
confidence: 99%